Adolescent cocaine differentially impacts psychomotor sensitization and epigenetic profiles in adult male rats with divergent affective phenotypes - Parsegian, Aram; García-Fuster, M. Julia; Hebda-Bauer, Elaine; Watson, Stanley J.; Flagel, Shelly B.; Akil, Huda (Frontiers in Psychiatry, 2022)
Adolescent drug use reliably predicts increased addiction liability in adulthood, but not all individuals are equally impacted. To explore the biological bases of this differential reactivity to early life drug experience, we used a genetic rat model of temperament and evaluated the impact of adolescent cocaine exposure on adult psychomotor sensitization. Relative to adult bred low-responder (bLR) rats, bred high-responders (bHR) are more sensitive to the psychomotor-activating effects of cocaine and reinstate drug-seeking behavior more readily following prolonged cocaine exposure and/or abstinence. We found that a 7-day sensitizing cocaine regimen (15 mg/kg/day) during either adolescence or adulthood produced psychomotor sensitization in bHRs only, while a dual cocaine exposure prevented further sensitization, suggesting limits on neuroplasticity. By contrast, adolescent cocaine in bLRs shifted their resilient phenotype, rendering them more responsive to cocaine in adulthood following adolescent cocaine. To begin to explore the neural correlates of these behavioral phenotypes, we assessed two functionally opposite epigenetic chromatin modifications implicated in addiction liability, permissive acetylation (ac) and repressive tri-methylation (me3) on Histone 3 Lysine 9 (H3K9), in four striatal sub-regions. In bHRs, decreased H3K9me3 and increased acH3K9 in the nucleus accumbens (NAc) core associated with cocaine sensitization. In bLRs, the combination of cocaine exposure in adolescence and adulthood, which lead to an increased response to a cocaine challenge, also increased acH3K9 in the core. Thus, adolescent cocaine experience interacts with genetic background to elicit different behavioral profiles relevant to addiction in adulthood, with concurrent modifications in the epigenetic histone profiles in the NAc that associate with cocaine sensitization and with metaplasticity.